O gênero Achyrocline (Less.) DC. (Asteraceae: Gnaphalieae) no Brasil - Deble, Leonardo Paz (2007)
Basically neotropical, the genus Achyrocline (Less.) DC. (including Stenophalium A. Anderb.) is most closely related with genera Pseudognaphalium Kirp. and Helichrysum Mill. Achyrocline has been considered as a separate genus due to its few-flowered (< 20), with few bracteis (< 30) in each capitula, as well as to the glabrous achenes, dotted with smooth epiderm walls, with longitudinal groove or imbricate papillae. Twenty five species are presently recognized to Brazil: Achyrocline alata (Kunth) DC., A. albicans Griseb., A. anabelae Deble, A. candicans (Kunth) DC., A. chionaea (DC.) Deble & Marchiori, A. conduplicata Deble sp. nov., A. crassiuscula (Malme) Deble & Marchiori, A. disjuncta Hemsl., A. eriodes (Mattf.) Deble & Marchiori, A. estevesiana Deble sp. nov., A. flaccida (Weinm.) DC., A. gardneri (Baker) Deble & Marchiori, A. gertiana Deble & Marchiori, A. glandulosa Blake, A. heringeri (H. Rob.) Deble & Marchiori, A. lanosa Deble sp. nov., A. luisiana Deble, A. marchiorii Deble, A.mathiolaefolia DC., A. ribasiana Deble & Marchiori, A. satureioides (Lam.) DC., A. sordescens Deble sp. nov, A. tombadorensis Deble & Marchiori, A. vargasiana DC. and A. vauthieriana DC. The main diversity centers in Brazil are the grasslands and open forests of the southern country as well as the highest elevations of the brazilian plateau, specially in the southeast and in part of northeast regions (Bahia); the lesser frequency, on the other hand, are in the center-west, northeast and north of Brazil. Taxonomic entities nomenclature is actuallized. The study also presents four new species (Achyrocline conduplicata, A. estevesiana, A. lanosa and A. sordescens), twelve new synonymities, a latin diagnose and a lectotype to Achyrocline crassiuscula. Descriptions, illustrations, maps of geographic distributions, vernacular names, the etymology, the synonymity and a key for all taxa, are also furnished.